STRUCTURE AND CONTENT OF I-, HE-IMAGES IN THE MINDS OF YOUNG PEOPLE LIVING IN THE REPUBLIC OF TUVA - S. M. Mombey-ool; V. L. Sitnikov (Вестник университета)
I-, He-images in the minds of young people, living on the territory of the republic of Tuva have been analysed in detail. An approach to the study of socio-perceptual characteristics in the minds of young people in the context of resilient behavior has been proposed, which will be interesting to specialists in the field of social perception, psychology of coping behavior and resilience. Special attention in the article has been paid to the content and structure of socio-perceptive features of images in the minds of young people. It has been proved in the paper that He-concept ensures consistency of ideas about other people, sometimes coordinating heterogeneous information about partners in communication. The authors have traced the knowledge about himself from different sides of human representations – about his volitional, communicative, bodily, material, spiritual, moral and behavioral characteristics, which make up a unique image of himself, form the I-concept of a person.